HUBUNGAN BODY IMAGE DAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KEBIASAAN MAKAN PADA REMAJA PUTRI DI SMAN 1 KOTA SERANG - Andini, Shafa; Malkan Bakhrul Ilmi, Ibnu; Wahyuningsih, Utami; Intania Sofianita, Nur (STIKes Mitra Keluarga, 2023)
Background: Nutritional problems in adolescent are caused by changes in eating habits. Several factors that influence changes in eating habits are body image and exposure to social media. Objective: This research wants to find out the relationship between body image and the intensity of social media use with the eating habits of young women at SMAN 1 Serang City. Methods: The research design used was a cross-sectional study with a sample size of 145 respondents and selected using a stratified random sampling technique.. Variables collected include eating habits, body image, and intensity of social media use. Data were analyzed using the chi-square test and Fisher's exact test. Results: There was an association between body image (p=0,001) and eating habits, and there were no association between frequency (p=0,288), duration (p=0,469), and intensity (p=0,715) of social media use and eating habits. Conclusion: There was an association between body image and eating habits and no association between frequency, duration, and intensity of social media use and eating habits of female adolescents